Knowledge, attitude, and practice of Kangaroo Mother Care among health providers in Depok General Hospital - Astri Fauziyah; Hadi Pratomo; Karina Samaria (Indonesian Journal of Perinatology, 2021)
Introduction: Low birth weight infants contribute to neonatal deaths. Kangaroo mother care (KMC) is a treatment with various benefits as an alternative to an incubator. In Depok General Hospital, its implementation was not yet optimal. This study aimed to assess kangaroo mother care knowledge, attitude, and practice among health providers. Methods: This descriptive study with a cross-sectional approach was conducted from November to December 2015 at Depok General Hospital. The population was all health providers in the study site. This study used total sampling (37 persons). The inclusion criteria were: health providers of Depok General Hospital who worked in the perinatology, delivery, rooming-in rooms, and obstetric polyclinic, had a minimum of 6 months working experience, agreed to become respondents. The exclusion criteria were: on work leave during the study period, on study assignment without working. The data were collected using a questionnaire. Univariate analysis was conducted using SPSS. Result: The mean age of respondents was 31.38 years, ranging from 23-41 years. The average working experience was 7.95 years. All respondents were female, 81.1% graduated from Diploma III, and 72.97 % had experienced or trained in KMC. About 75.7% of respondents had good knowledge of KMC, 51.4% had a positive attitude towards KMC, and 64.9% had a low level of KMC practice. Conclusion: The majority of the respondents had good knowledge of KMC, around half had a positive attitude towards KMC, and more than half had a low level of KMC practice. Training, facilities, written SOP, and management commitment for KMC are needed for successful KMC implementation.